Recent advances in the extraction technology and bioactivity of lentinan - Sizhu Ren; Chunyan Xie; Hua Liu; Liyan Li; Xiaoling Han; Wenjie Chen (Journal of Functional Foods)
The mycelia and fruiting bodies of Lentinula edodes are rich in polysaccharides that are widely studied for their edible and medicinal properties. Many advanced technologies have been applied for lentinan extraction, such as ultrasonic-assisted, microwave-assisted, and enzyme-assisted extractions. However, their advantages and disadvantages differ, which directly affect the structural and functional properties of lentinan. Compared with traditional methods, these advanced technologies have the advantages of high extraction efficiency, short operation time, low energy consumption, and low solvent consumption. Based on a summary of the extraction methods and biological functions of lentinan, this review article concentrates on the current literature on the extraction of lentinan, its chemical composition, and medicinal mechanisms. In addition, future research topics are also proposed.